Thomas Hobbes on Human Rights and Its Relevance to The Populist Movement in Indonesia - Wijanarko, Robertus; Riyanto, F.X. Armada (Politika: Jurnal Ilmu Politik, 2021)
This study deals with the political theory of Thomas Hobbes and its implications to the political dynamism in Indonesia. The aim of this research is to analyze the philosophical concept of Hobbes on human rights and the theory of liberalism, and its relevance to the current situation in Indonesia, which has recently been exposed to the politics of populism. The presence of the populist movement is not new in Indonesia; but the rise of the politics of identity, it could threaten the protection of human rights and liberal democracy. We utilize the methodology of text analysis based on Hobbes’s original writing, Leviathan, and his other political treatises to explore his account on human rights and liberalism, and then employ Hobbes’s thoughts to investigate the phenomenon of populism. We divide the study into two sections, the first deals with the philosophy of human rights which Hobbes elucidates in the perspective of his hypothetical notion of the state of nature, the concept of authority, and his theory of liberalism; the second discusses populism in Indonesia today. The study found that the concept of human rights and liberalism would lead to awareness of mutual respect in society, while the populist movement becomes a real challenge to the implementation of human rights and the development of liberal democracy. The philosophy of human rights is in accordance with the political dynamism of Indonesian society. On the contrary, the populist movement could possibly plunge the country into a conflictual precipice of religious, racial-regional, and socio-political identities.